Evaluation of the Use of Antibiotics in Covid-19 Patients at X Muara Bulian Hospital in 2022 - Rizky Amalia , Yola; Rasmala DEWI; Deny SUTRISNO (RADINKA JAYA UTAMA PUBLISHER, 2024)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus2 (SARSCoV2). Treatment for COVID-19 is still uncertain, so various treatment efforts have been carried out, including administering antibiotics. This research is a type of non-experimental research and uses a descriptive research design. Data collection was carried out retrospectively. Data collection from medical records of COVID-19 patients in 2022 at Hospital X Muara Bulian. The population of 86 patients, a sample of 46 patients. The research results showed that 69.57% of patients were male, 32.61% of patients were aged 36–45 years, and Covid-19 patients received the most antibiotic therapy, namely azithromycin in the macrolide group at a dose of 500 mg for 5 days with a percentage of 69.57%, The accuracy of the indication, dose, and duration of administration of antibiotics is 100% following the COVID-19 Management Guidelines, Edition 2 of 2020, and no drug interactions have occurred. This research is based on existing literature. It is hoped that future researchers will use a larger sample size than this study so that they can understand demographic characteristics, patterns of antibiotic use, rational use of drugs, and drug interactions that occur.